2019
DOI: 10.1111/ppl.13032
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic difference in secondary metabolism‐related enzyme activities and their relative gene expression patterns, osmolyte and plant hormones in wheat

Abstract: Salinity and drought are the two most important and frequently co-occurring abiotic factors. A greenhouse pot experiment was carried out on two contrasting wheat genotypes (Jimai22, salt tolerant; Yangmai20, salt sensitive) to analyze the effect of drought (4% soil moisture content, D) and salinity (100 mM NaCl, S) either individually or combined on secondary metabolism-related enzyme activities and osmolytes. Results showed that drought, salinity and their combination (D + S) caused increases in phenylalanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In this study, the highest increase of activity of SKDH under saline stress in the roots and leaves was detected in CM72, but the increase in wheat cultivars was very small. Consistent with this finding, Ahmad et al (2015) [37] reported a boosted SKDH enzyme activity in barley genotypes and Tesfaye et al (2019) [38] in wheat genotypes under combined stress of drought and salinity.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the highest increase of activity of SKDH under saline stress in the roots and leaves was detected in CM72, but the increase in wheat cultivars was very small. Consistent with this finding, Ahmad et al (2015) [37] reported a boosted SKDH enzyme activity in barley genotypes and Tesfaye et al (2019) [38] in wheat genotypes under combined stress of drought and salinity.…”
Section: Discussionmentioning
confidence: 67%
“…The formation and accumulation of secondary metabolites in medicinal plants are regulated by a variety of factors. In recent years, environmental factors, hormone regulation, and the expression and regulation of functional genes had often been reported (Martins et al, 2018;Ibrahim et al, 2019;Dugasa et al, 2020). The early results showed that the growth period of suspension culture callus was about 40 days: the slow growth period was 0-9 days; the exponential growth period was 12-24 days; the platform period is 27-39d; the decline period was 39 days after culture (Supplementary Figure 7).…”
Section: Discussionmentioning
confidence: 91%
“…Increased drought has a significant impact on plant growth and development, resulting in a notable decline in cereal yields, including durum wheat ( Triticum turgidum ssp. durum ), which is one of the most important cereal crops grown worldwide [ 5 ]. In this framework, the rediscovery of ancient varieties with their wide genetic diversity is a promising strategy to improve wheat fitness in light of climate change.…”
Section: Introductionmentioning
confidence: 99%